2016
DOI: 10.1016/j.ajhg.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Isolated and Syndromic Retinal Dystrophy Caused by Biallelic Mutations in RCBTB1 , a Gene Implicated in Ubiquitination

Abstract: Inherited retinal dystrophies (iRDs) are a group of genetically and clinically heterogeneous conditions resulting from mutations in over 250 genes. Here, homozygosity mapping and whole-exome sequencing (WES) in a consanguineous family revealed a homozygous missense mutation, c.973C>T (p.His325Tyr), in RCBTB1. In affected individuals, it was found to segregate with retinitis pigmentosa (RP), goiter, primary ovarian insufficiency, and mild intellectual disability. Subsequent analysis of WES data in different coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 68 publications
3
26
0
Order By: Relevance
“…Mutations in this gene have also been observed to be the causal factor for syndromic POI. 61 Hormones play an essential role in regulating folliculogenesis. The entire menstrual cycle is tightly regulated by the function of gonadotropin hormones and their receptors.…”
Section: Genetics Of Primary Ovarian Insufficiencymentioning
confidence: 99%
“…Mutations in this gene have also been observed to be the causal factor for syndromic POI. 61 Hormones play an essential role in regulating folliculogenesis. The entire menstrual cycle is tightly regulated by the function of gonadotropin hormones and their receptors.…”
Section: Genetics Of Primary Ovarian Insufficiencymentioning
confidence: 99%
“…Sequencing studies have recently found that mutations in NMNAT1 can cause LCA and these constitute approximately 10% of unsolved cases (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). The majority of NMNAT1 mutations found in LCA patients are missense, with a small portion are nonsense and frameshift.…”
Section: Introductionmentioning
confidence: 99%
“…Over two million people worldwide are affected by inherited retinal degenerations (IRDs), a family of blinding diseases characterized by progressive death and dysfunction of primarily rod and cone photoreceptors 1,2 . Pathogenic variants (PVs) in over 270 genes have been associated with IRDs 3 , many of which were discovered recently by virtue of advances in sequencing technologies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . However, despite substantial progress in genetic methodologies, current strategies can genetically solve only about 55-60% of IRD cases [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%
“…The remaining missing diagnoses are in part due to new, yet to be discovered IRD genes. However, PVs in each new disease gene are rare, affecting a handful of IRD patients [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] , suggesting that the missing genetic causality largely lies in the known IRD genes. A considerable proportion of these elusive PVs are due to structural variations (SVs) such as copy number variations (CNVs), or deep intronic variants that affect splicing 36,[39][40][41][42][43][44][45][46][47][48][49] , which are not readily available from the standard output of targeted next generation sequencing (NGS) pipelines.…”
Section: Introductionmentioning
confidence: 99%